Locally enhanced early bone formation of zoledronic acid incorporated into a bone cement plug in vivo. (27th September 2012) - Sörensen, Torben C.; Arnoldi, Jörg; Procter, Philip; Beimel, Claudia; Jönsson, Anders; Lennerås, Maria; Emanuelsson, Lena; Palmquist, Anders; Thomsen, Peter; Robioneck, Bernd; Steckel, Hartwig
Abstract Objectives The aim of the study was to gain experience about the short‐term effects of zoledronic acid (ZOL) on bone‐implant contact (BIC), bone regeneration and bone area (BA). Methods In this in‐vivo study, ZOL was released locally from a drug‐loaded pre‐shaped calcium phosphate bone cement plug which was implanted into a bone defect in the proximal tibia of rats. At 1 and 3 weeks post implantation, tissue reactions as well as bone regeneration capabilities at the implant site were investigated. Furthermore, tissue samples, harvested at placebo and verum plug sites were used to analyse the gene expression of selected bone‐specific markers by using quantitative polymerase chain reaction. Data were normalized against ribosomal RNA (Rn18s) subunits. Key findings In the placebo interface a higher amount of cells could be detected as indicated by higher expression of small subunit Rn18s. Nevertheless, comparing the normalized data of the selected gene expression levels, no significant differences were detected. The histomorphometric results showed a significant higher BIC and BA for ZOL‐loaded plugs at 3 weeks after implantation. Conclusions In this model, ZOL was demonstrated to be effective in impacting the bone regeneration process towards reduction of early bone resorption and enhanced bone formation.